2012
DOI: 10.7314/apjcp.2012.13.10.5043
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc Status and Helicobacter Pylori Infection in Gastric Disease Patients

Abstract: The role of Helicobacter pylori status and serum zinc value in gastric disease patients and healthy controls were investigated. Cases used in this work were 45 gastric cancer patients, 44 with peptic ulcers, 52 suffering gastritis and 64 healthy controls, all diagnosed histologically with the controls undergoing medical checkups. Helicobacter pylori status and serum levels of Zn were determined by 13C-urea breath test and flame atomic absorption spectrophotometer, respectively. Our study showed that Helicobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…In the studies by Tanir et al (27) and Demirkirap et al (28), age did not have an effect on the incidence of cancer, while in another study by Dehaven et al (29), the rate of cancer increased with age increasing. The mean serum zinc level in patients with gastric adenocarcinoma was lower than that in patients with other gastrointestinal cancers with a significant difference similar to the studies of Zhang et al study (13), Li et al (14).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the studies by Tanir et al (27) and Demirkirap et al (28), age did not have an effect on the incidence of cancer, while in another study by Dehaven et al (29), the rate of cancer increased with age increasing. The mean serum zinc level in patients with gastric adenocarcinoma was lower than that in patients with other gastrointestinal cancers with a significant difference similar to the studies of Zhang et al study (13), Li et al (14).…”
Section: Discussionsupporting
confidence: 85%
“…Generally, the consequent of zinc activity in the body reduces the number of tumor cells and decreases tumor volume (12). The results of some studies showed a difference in the serum levels of zinc between the patients with gastrointestinal cancers and healthy individuals (13)(14)(15)(16). According to the high prevalence of gastrointestinal cancers and the role of zinc in delaying oxidative reactions we intended to conduct a study on this subject.…”
Section: Key Pointmentioning
confidence: 99%
“…(10) Zn is trace element found in blood, and most of it is contained in bones, skins, and hair (approximate 70%). Inverse associations were also obtained between serum Zn and risk of gastric cancer in some early studies, (11,12) but not all. (13) Higher level of Cu alone was also found significantly higher in cancerous human stomach in compared to normal samples.…”
Section: Introductionmentioning
confidence: 91%
“…Gulmira Nigmetzhanovna Kulmambetova 1 *, Мeruert Kuatbekovna Imanbekova 1 , Аndrey Alexeevich Logvinenko 2 , Аdilbek Temirzhanovich Sukashev 2 , Мaxim Leonidovich Filipenko 3 , Еrlan Mirhaidarovich Ramanсulov 1 with gastritis increasing the risk of gastric cancer (Zhang et al, 2012). From another study exists evidence that key factor in development of gastric cancer p53 gene intron alterations may contribute gastritis development and early detection of these alterations in precancerous lesions such as gastritis may be useful for prediction of risk developing of gastric cancer (Najjar Sadeghi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%